MINDFULNESS BASED STRESS REDUCTION (MBSR) TERHADAP PENURUNAN BURNOUT PADA PERAWAT - Sarah Fatimah Azzahra; Evany Victoriana; Maria Yuni Megarini (Universitas Islam Indonesia, 2023)
ABSTRACT: Nurse is one of the professions engaged in the health sector and has a high intensity to deal directly with patients. The many responsibilities, the high complexity of the work and the demands that must be carried out by nurses make the nursing profession vulnerable to stress and burnout at work. This study aims to determine the effect of mindfulness-based interventions on reducing burnout in nurses at